Chewable tablets containing rape bee pollen and maca attenuate testosterone propionate–induced benign prostatic hyperplasia in Sprague–Dawley rats by regulating the gut microbiota and modulating the IL-6/JAK2/STAT3 signaling pathway - Huang, Xiaoqiang; Ru, Guohua; Tian, Hengyun; Zhang, Pengbo; Zhao, Hongchang; Zhang, Shouren; Wang, Sijie; Jia, An; Zhao, Wanli (Frontiers in Microbiology, 2025)
BackgroundBenign prostatic hyperplasia (BPH) significantly compromises patients' quality of life, has detrimental effects on both physical and mental well-being, and poses a substantial economic burden. Current pharmacological interventions primarily focus on symptom relief; nevertheless, their associated adverse effects are evident. Rape bee pollen and maca are both homologous food products, which are not only rich in nutrition, but also have many biological activities. There is no report on the combination of rape bee pollen and maca in benign prostatic hyperplasia therapy, and no report on the molecular mechanism. This study aims to systematically investigate the therapeutic efficacy and underlying molecular mechanisms of a chewable tablet formulation containing rape bee pollen and maca in the management of BPH.MethodsFirst, the chewable tablets were prepared from rape bee pollen and maca, and the High Performance Liquid Chromatography (HPLC) fingerprint was established. During a 4-week period, rats were subjected to subcutaneous injections of testosterone propionate solution to establish a BPH model, while simultaneously receiving orally administered chewable tablets for BPH treatment via gavage. We assessed the body weight, prostate tissue index, serum levels of dihydrotestosterone (DHT), testosterone (T), estradiol (E2), interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), interleukin-1beta (IL-1β), superoxide dismutase (SOD), malondialdehyde (MDA) and glutathione (GSH) levels in rats. Prostate tissues were collected for histopathological analysis. The protein expression levels of IL-6, phosphorylated Janus kinase 2 (p-JAK2), and phosphorylated signal transducer and activator of transcription 3 (p-STAT3) were determined by Western blotting. Rat feces were collected aseptically for 16S rDNA gene sequencing to assess gut microbiota levels. Additionally, our research findings demonstrate that the combined application of rape pollen and maca exhibits superior therapeutic efficacy compared to the individual use of either rape pollen or maca alone.ResultsWe prepared the rape bee pollen and maca chewable tablets, established the HPLC fingerprint map, and quantitatively analyzed four of these main components. We found that the rape bee pollen and maca chewable tablets significantly inhibited DHT, T, E2, E2/T ratio, IL-6, TNF-α, and IL-1β and reduced MDA levels and increased SOD, GSH levels. 16S rDNA gene sequencing revealed that the chewable tablet increased the abundance of the beneficial bacteria Faecalibacterium, Collinsella, Phascolarctobacterium, Kineothrix, and Lactobacillus, and decreased that of the pro-inflammatory bacterium Prevotella. Western blot indicated that the chewable tablet could significantly inhibit the IL-6, p-JAK2, and p-STAT3 protein expression levels.ConclusionWe found that rape bee pollen and maca chewable tablets had a protective effect on rats with BPH, and also found that the combination of rape bee pollen and maca was better than separate application. The mechanism may be related to the gut microbiota and IL-6/JAK2/STAT3 signaling pathway.